A first-generation integrated tammar wallaby map and its use in creating a tammar wallaby first-generation virtual genome map - Wang, Chenwei (BioMed Central, 2011)
BACKGROUND: The limited (2X) coverage of the tammar wallaby (Macropus eugenii) genome sequence dataset currently presents a challenge for assembly and anchoring onto chromosomes. To provide a framework for this assembly, it would be a great advantage to have a dense map of the tammar wallaby genome. However, only limited mapping data are available for this non-model species, comprising a physical map and a linkage map. RESULTS: We combined all available tammar wallaby mapping data to create a tammar wallaby integrated map, using the Location DataBase (LDB) strategy. This first-generation integrated map combines all available information from the second-generation tammar wallaby linkage map with 148 loci, and extensive FISH mapping data for 492 loci, especially for genes likely to be located at the ends of wallaby chromosomes or at evolutionary breakpoints inferred from comparative information. For loci whose positions are only approximately known, their location in the integrated map was refined on the basis of comparative information from opossum (Monodelphis domestica) and human. Interpolation of segments from the opossum and human assemblies into the integrated map enabled the subsequent construction of a tammar wallaby first-generation virtual genome map, which comprises 14336 markers, including 13783 genes recruited from opossum and human assemblies. Both maps are freely available at http://compldb.angis.org.au. CONCLUSIONS: The first-generation integrated map and the first-generation virtual genome map provide a backbone for the chromosome assembly of the tammar wallaby genome sequence. For example, 78% of the 10257 gene-scaffolds in the Ensembl annotation of the tammar wallaby genome sequence (including 10522 protein-coding genes) can now be given a chromosome location in the tammar wallaby virtual genome map.